Hyperfine interaction vs. spin–orbit coupling in organic semiconductors. Issue 112 (23rd November 2016) - Niu, L. B.; Chen, L. J.; Chen, P.; Cui, Y. T.; Zhang, Y.; Shao, M.; Guan, Y. X.
Abstract : We report experimental and theoretical studies on hyperfine interaction vs. spin–orbit coupling in a thin film of organic semiconductor poly[9, 9-di- n -hexylfluorenyl-2, 7-diyl] and the dramatic influence of doping the PFO with bis[2-(2′-benzothienyl)pyridinato- N, C 3′]Ir(acac). Abstract : Organic semiconductors have shown magnetic field responses in electrical currents. This phenomenon has been generally attributed to hyperfine interaction (HFI) and spin–orbit coupling (SOC). For the first time, we report the experimental and theoretical studies on hyperfine interaction vs. spin–orbit coupling in one thin film of organic semiconductor poly [9, 9-di- n -hexyl-fluorenyl-2, 7-diyl] and the dramatic influence of doping the PFO with complexes of bis [2-(2′-benzothienyl)-pyridinato- N, C3′] iridium (acetyl-acetonate). The intra-molecular HFI and SOC are only dependent on the intra-molecular interaction among electrons, nuclei and orbital field in a given molecule. Phosphorescence and fluorescence spectroscopies were used to measure the spin–orbit coupling strength. Furthermore, HFI is a short-range interaction and inter-molecular HFI is negligible. Inter-molecular SOC depends not only on molecular structure but also distance between adjacent molecules. Inter-molecular SOC strength increases strongly when the distance between adjacent molecules is decreased.